Screening of a panel of steroid-related genes showed polymorphisms of aromatase genes confer susceptibility to advanced stage endometriosis in the Taiwanese Han population - Cheng-Hsuan Wu; Jyuer-Ger Yang; Yu-Jun Chang; Chao-Chin Hsu; Pao-Lin Kuo (Elsevier, 2013)
Objective: To establish a multilocus model for studying the effect of steroid-related genes on advanced stage endometriosis. Materials and methods: A total of 121 patients with advanced stage endometriosis and 171 control women were included. Eighteen single-nucleotide polymorphisms (SNPs) from nine genes (HSD17B1, HSD17B2, HSD17B5, HSD17B6, CYP17, CYP19, ERα, ERβ, and PGR) were genotyped using the TaqMan assays. Logistic regression models were used to evaluate the genetic effects, with adjustment for other covariates. Results: Only the presence of the mutant CYP19 (aromatase gene) was associated with a significantly increased risk of endometriosis after adjusting for age, BMI, and parity (p = 0.002, OR = 2.69; 95% CI = 1.44-5.02). No association was ascertained between the other investigated SNPs and endometriosis. Conclusion: Polymorphisms of the aromatase gene confer susceptibility to advanced stage endometriosis in the Taiwanese Han population.